“English First” APK for Facilitating Autonomous Screenagers - Suprianti, G. A. P.; Santosa, Made Hery; Putra, Made Agus Mandala; Jayanta, I Nyoman Laba (Universitas Pendidikan Ganesha, 2021)
Digital native or screenagers cannot be separated from technology in their education and entertainment (edutainment). That phenomenon gives them an opportunity to be autonomous learners. Regarding the principle of autonomous learners, this study was aimed at developing an Android Package Kit (APK) smartphone application as learning media for facilitating screenagers. A research and development design comprising need analysis, design, and development was employed during the study. Freshmen year of English Language Education who attended English Intensive Course (IEC) were involved in the study. The data were collected through students’ interview guide, document analysis, expert judgment rubrics, and a questionnaire. The result showed that the freshmen year needed innovative, challenging, and fun English learning media in the course. In addition, the application was developed based on five topics found in the document analysis, namely “Meeting at the Campus”, “What You Are Wearing”, “Directions”, “Weather”, and “Necessity and Obligation”. From the result of the expert judgment, the learning media were considered excellent. Both learners and lecturers in this digital era should consider the needs of utilizing technology in teaching and learning process specifically for facilitating autonomous learners.